Analysis of energy utilization in banana (Musa spp.) cultivation in Malaysia: a case study in smallholder farming / Nordin Onsang - Onsang, Nordin (Faculty of Plantation and Agrotechnology, 2019)
Banana (Musa spp.) is one of the major staple foods in Asia and Africa. In Malaysia, the production of banana has exceeded the need for local consumption and creating the opportunity to make banana as one of the exported fruits. As a non-seasonal fruits make it easy to cultivate banana over the year. The current study was conducted to analyse the utilization of energy input in banana cultivation in Malaysia. The study also aimed to inform the input used in banana cultivation with the pattern of energy produce to create reference for planting banana with effective management. Data were collected based on oral interviews with the owner of the banana cultivation at Kampung Durian Tunjung Wilayah Persekutuan Labuan. The collection of data get from the oral interview was record and analyse using the Microsoft Excel Spreadsheet. Result shows that the highest energy input used in banana cultivation was the chemical fertilizer, contributing to 49.93% from the total energy equivalents used in the cultivation. Water irrigation was the second highest energy input with a segment of 29.17% of the total energy input, followed by herbicide, human labor, farm yard manure, fuel and machinery at 9.15%, 7.04%, 3.95%, 0.51% and 0.24%, respectively. The banana cultivation in the study area produce 1.00 ratio of energy output/input. As conclusion, the cultivation of banana utilizes the energy effectively due to the ratio of energy output/input produce is equal to 1. To increase the ratio, the use of suitable machinery and proper technology is required in the cultivation of banana in Malaysia. This will increase the efficiency of energy utilization in banana cultivation.